Answer

Verified

430.2k+ views

**Hint:**In order to solve this problem we need to know that we need to find the value of a, b, c by using differentiation and partial differentiation. We first need to find the value of a and b with the help of the information given to get the exact function f(x). Doing this and proceeding will give you the right answer.

**Complete step-by-step solution:**It is given that,

$f(x) = a{x^2} + bx + c$

And $f(x + y) = f(x) + f(y) + xy\forall y \in R$

And $a + b + c = 3$

On differentiating f(x) with respect to x we get,

$f(x) = 2ax + b$

$f’(0) = b$

since $f(x+y) = f(x) + f(y) + xy$

Then we put x = y = 0

$f(0+0) = f(0) + f(0) + 0$

That is $f(0) = 0$

Partial differentiation w.r.t x we get,

$f’(x+y) = f’(x) + y$

Put x = 0 in this equation.

Then we get,

$f‘(y) = f’(0) + y$

$f’(y) = b’ + y (f’(0) = b)$

On integrating we get,

$f(y) = b’y + \dfrac{{{y^2}}}{2} + c'$

On putting y = x we get

$f(x) = \dfrac{{{x^2}}}{2} + bx + c’$

Put x = 0 we get,

$f(0) = c’ = 0$

On comparing with given function the given function with f(x) we get,

$a = \dfrac{1}{2}, b’ = b, c’ = c = 0$.

Then the equation $a + b + c = 3$ can be $\dfrac{1}{2} + b’ + 0 = 3$

Then the value of b’ = $\dfrac{5}{2}$.

Then the equation f(x) we get as,

$f(x) = \dfrac{1}{2}{x^2} + \dfrac{5}{2}x$

Now we have to find $\sum\limits_{n = 1}^{10} {f(n)} $

$\sum\limits_{n = 1}^{10} {f(n)} = \sum {\dfrac{1}{2}{n^2} + \sum {\dfrac{5}{2}n} } $

So on opening the summation we get the value as,

\[\sum\limits_{n = 1}^{10} {f(n)} = \dfrac{1}{2}\dfrac{{n(n + 1)(2n + 1)}}{6} + \dfrac{5}{2}\dfrac{{n(n + 1)}}{2}\]

On putting n= 10 we will get the value of \[\sum\limits_{n = 1}^{10} {f(n)} \]

\[\sum\limits_{n = 1}^{10} {f(n)} = \dfrac{1}{2}\dfrac{{10(10 + 1)(2(10) + 1)}}{6} + \dfrac{5}{2}\dfrac{{10(10 + 1)}}{2}\]

On solving it we get,

\[\sum\limits_{n = 1}^{10} {f(n)} = 192.5 + 137.5 \]

\[\sum\limits_{n = 1}^{10} {f(n)} = 330 \] is the answer to this problem.

**Hence option A is the correct answer.**

**Note:**Whenever we face such a type of question and always try to solve with partial differentiation it becomes very easy to tackle the question. First, always try to find the equation then apply the property of summation. You need to know that the sum of n natural number is \[\dfrac{{n(n + 1)}}{2}\] and that of ${n^2}$ is \[\dfrac{{n(n + 1)(2n + 1)}}{6}\]. Knowing this will help you to solve the problems further.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Which are the Top 10 Largest Countries of the World?

10 examples of evaporation in daily life with explanations

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Difference Between Plant Cell and Animal Cell